Perspektif Kanker di Kota Padangsidimpuan: Tindakan Medis dan Realitas Terkni - Olivia Feby Mon Harahap (Universitas Aufa Royhan, 2024)
Cancer is a cell that grows autonomously and uncontrollably and can then invade the surrounding organ tissue and have an impact on organ disorders. Based on observations at the Padangsidimpuan City General Hospital in the interval October to December 2023, it can be seen that there are 20 patients who have cancer. The types of cancer found include spinal cancer, virgin cancer, laryngeal cancer, and so on. This research is also based on obtaining data or information through observations or surveys and interviews with patients and stakeholders related to cancer treatment in Padangsidimpuan. Various techniques are used in cancer treatment, including surgical intervention, chemotherapy, radiotherapy, targeted therapy, and immunotherapy. In addition, the medical team is responsible for controlling the side effects of treatment that may occur and providing supportive care, such as psychological support and pain management. These methods are intended to improve the patient's quality of life and provide comprehensive care that considers various aspects of cancer treatment.